Transportation Challenges in Fertilizer Supply Chain in Malawi - Zuhra Junaida Mohamad Husny Hamid; Gryson Kondwani Chibwatiko Msuku; Moeinaddini Mehdi (International Journal of Supply Chain Management, 2020)
The high cost of fertilizer had left many small holder farmers unable to access fertilizer which resulted in low agricultural production in Malawi. To solve this problem, the government introduced the Farm Input Subsidy Program (FISP) in 2004/2005 growing season. The subsidy program constituted about 60% of all fertilizer imports into the country. But besides huge investment into this program, food insecurity situation had not been eliminated leaving many smallholder farmers depending on food handouts to take them to the next harvesting season. Policy makers are still exploring options on how to exploit the benefits of FISP. It is for this reason that an investigation was conducted on transportation challenges in fertilizer supply chain, as late delivery was reported to be one of the problems in the distribution process. The research objectives were to investigate the fertilizer supply chain challenges in Malawi, determine transportation challenges in the distribution of FISP fertilizer and recommend solutions for effective fertilizer distribution. To achieve this, a pragmatic philosophy was adopted by employing both qualitative as well as quantitative research methods in data collection. A snowball sampling method was used with the assistance of Road Transport Operators Association (RTOA) in Malawi. Three managers from both public as well as private fertilizer companies were interviewed while 38 questionnaires were administered to transporters that had been involved in subsidy fertilizer distribution. The findings of the research spotted logistical problems in the process of awarding contracts to fertilizer importers as well as transporters as not effective. Other findings included problems with beneficiary identification, high transportation costs, not utilizing ICT, ITS and lack of Research and Development as other challenges affected productivity. The research came up with a Roadmap to Fertilizer Supply Chain as a reference material to future fertilizer supply chain studies, proposed â€œgroup fertilizer procurementâ€ in future fertilizer procurement policies and provided empirical evidence of transportation challenges affecting fertilizer distribution in Malawi.